Performance of a PEM water electrolyser combining an IrRu-oxide anode electrocatalyst and a short-side chain Aquivion membrane. (9th November 2015) - Siracusano, S.; Baglio, V.; Moukheiber, E.; Merlo, L.; Aricò, A.S.
Abstract: An Ir0.7 Ru0.3 Ox nanosized anode electrocatalyst was coupled to an Aquivion short-side chain perfluoro-sulfonic acid membrane (120 μm; EW: 870 g/eq) for operation in a PEM electrolyser. A conventional carbon supported Pt catalyst was used as cathode. An excellent performance, of 4 A cm −2 at 1.9 V at 90 °C, was achieved for this electrolyser configuration in the presence of a moderate noble metal loading (1.5 mg cm −2 Ir + Ru; 0.5 mg cm −2 Pt). The interface of IrRuOx with Aquivion provided a 10% enhancement in performance compared to an equivalent interface with a Nafion membrane of similar thickness but characterized by a larger equivalent weight (EW: 1100 g/eq). The enhanced performance essentially derived from a decrease of polarization resistance. This appeared to be due to better interface characteristics between the electrodes and Aquivion ® ionomer giving rise to an increased catalyst utilization. Whereas, no significant change in Tafel slope and activation energy was recorded indicating a similar reaction mechanism. Highlights: IrRuOx is coupled to an Aquivion perfluoro-sulfonic acid membrane for electrolysis. Electrolysis performance of 4 A cm −2 at 1.9 V at 90 °C is achieved. Aquivion provides an enhancement in performance vs. Nafion membrane. Lower polarisation resistance is registered with Aquivion.